Rebranding of a corporate division after an acquisition - Urbanová, Klára; San José Iglesias, Rafael; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis aims to analyse the creation of a new brand image and the development of appropriate brand communication for a new rebranded division. In this thesis, qualitative mixed methods will be used consisting of (i) a content analysis of marketing communications and (ii) a thematic analysis of an in-depth interview. The research findings will provide a better understanding of (i) the creation and transformation of key brand elements, (ii) communication of the rebranding to different stakeholders, and (iii) choosing the proper rebranding strategy for the rebranding process of a division undergoing an acquisition. Before starting a rebranding process, it is crucial to establish a proper strategy and focus on both external and internal communication in order to keep all stakeholders' trust. This study investigates the recent rebranding process of Olympus Corporation's division acquired by an investment firm Bain Capital and examines the most important changes on key brand elements and the selection of a proper rebranding strategy considering internal and external stakeholders.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses